Factors to Improve the Management of Hepatitis C in Drug Users: An Observational Study in an Addiction Centre - Joseph Moussalli; Helene Delaquaize; Dominique Boubilley; Jean Pierre Lhomme; Jules Merleau Ponty; David Sabot; Anne Kerever; Marc Valleur; Thierry Poynard (Gastroenterology Research and Practice)
Barriers to management of HCV in injection drug users are related to patients, health providers, and facilities. In a primary care drug user's addiction centre we studied access to HCV standard of care before and after using an onsite total care concept provided by a multidisciplinary team and noninvasive liver fibrosis evaluation. A total of 586 patients were seen between 2002 and 2004. The majority, 417 patients, were HCV positive and of these patients 337 were tested positive for HCV RNA. In 2002, patients were sent to the hospital. with the Starting of 2003, patients were offered standard of care HCV management in the center by a team of general practitioners, a consultant hepatologist, psychiatrists, nurses, and a health counsellor. Liver fibrosis was assessed by a non invasive method. In 2002, 6 patients had liver fibrosis assessment at hospital facilities, 4 patients were assessed with liver biopsy and 2 patients with Fibrotest-Actitest. 2 patients were treated for HCV at hospital. In 2003 and 2004, 224 patients were assessed with Fibrotest-Actitest on site. Of these, 85 were treated for HCV. SVR was achieved in 43%. We conclude that the combination of an onsite multidisciplinary team with the use of a noninvasive assessment method led to improved management of HCV infection in drug users' primary care facility.